Research Proposal Development in the Age of Generative AI: Exploring Students’ Difficulties and the Emergence of AI-Driven Competence Illusion - Fikry Firmansyah; Abdul Basid; Fajar Alfaris; Moch. Danu Kurniadi (Global Education Journal, 2026)
This research is motivated by the discovery of various difficulties for students in preparing thesis proposals in the Research Methodology course, both in methodological, academic, and psychological aspects. This condition has an impact on the low quality of student research proposals and the lack of optimal understanding of research methodology. This study aims to analyze the forms of student difficulties, the causative factors, and their implications for the learning of Research Methodology in Islamic private universities. The research uses a qualitative approach with a case study design. Data was obtained through in-depth interviews, learning observations, and analysis of student proposal documents. The research informants consist of fifth-semester students and lecturers in the Research Methodology course at STAI Ali bin Abi Thalib Surabaya. Data analysis was carried out using the interactive model of Miles, Huberman, and Saldana through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that students have difficulties in understanding the concept of research methodology, composing theoretical studies critically, developing coherent academic paragraphs, and applying scientific writing techniques appropriately. In addition, it was found that there was a high level of academic anxiety and low student learning independence. This study also found the phenomenon of AI-driven competence illusion, which is a condition when students produce proposals that appear systematic through the help of generative AI, but have not yet understood the substance of the research methodology in depth. The findings of this study provide important implications for the development of research methodology learning strategies that are more contextual, applicative, and oriented towards strengthening student research literacy.